Penerapan Teori Belajar Konstruktivisme dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa - Azizah Siti Lathifah; Khoirunisa Hardaningtyas; Pratama, Zarir Abiyyuda; Moewardi, Istar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Student activeness affects student learning outcomes. Active students tend to be involved in interacting with teachers or other students in the process of discussion and question and answer to gain useful knowledge. The application of an effective learning model can increase student activeness so that it will also affect student learning outcomes. One of the learning approaches that is often used in learning is the approach of applying constructivism learning theory. The purpose of this study is to examine the impact of constructivism learning theory on student activeness and learning outcomes. This research uses literature study as its method. Data was collected by reviewing several previous studies related to constructivism learning theory and its effect on students' activeness and learning outcomes. The collected data was then compiled, analyzed, and concluded to get a conclusion about the impact of constructivism learning theory. The results show that constructivism theory can be applied in learning by providing opportunities for students to learn by doing in a comfortable learning environment, so as to increase student activeness and learning outcomes.